OPTIMIZATION STRATEGY OF MURABAHAH FINANCING AT KSPPS BMT NUSA UMMAT PRAGAAN - Yusri, Moh; Putra, Rizal Johan; Mubarok, Muhamad Khusni (Ngejha, 2024)
This study aims to analyze the strategy of optimizing murabahah financing at KSPPS BMT Nusa Ummat, Pragaan District, Sumenep Regency. Murabahah financing is one of the important instruments in Islamic finance that is widely used to support micro, small, and medium enterprises (MSMEs). However, in its implementation, there are various challenges that can affect the effectiveness of the financing, such as credit risk and suboptimal management. This study uses a qualitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation studies. The results of the study show that effective optimization strategies include strengthening risk management, improving service quality, and applying technology in operational processes. By implementing this strategy, it is hoped that KSPPS BMT Nusa Ummat can improve the efficiency and effectiveness of murabahah financing, as well as contribute more to local economic development.